The significance of behavioural communication in Malaysian academia and media studies / Muhammad Azril Izuan Ramlan ... [et al.]. - Ramlan, Muhammad Azril Izuan; Ab Rashid, Faridah Hanem; Khairul Anuar, Nurliyana Kamilah; Amanah, Farah Hazween; Hassan @ Asan, Amirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In the vibrant tapestry of Malaysian academia, mastering the art of behavioural communication is not just a skill but a fundamental aspect of personal and professional growth. With its diverse cultural landscape and dynamic social dynamics, Malaysia presents a unique context where effective communication transcends linguistic boundaries and delves into the realm of behavioural nuances. From a student’s perspective, understanding and applying behavioural communication principles can significantly impact academic performance, interpersonal relationships, and future career prospects. In lecture halls and seminar rooms across Malaysian universities, students are not merely passive recipients of knowledge but active participants in a complex web of interpersonal interactions. The impact of non-verbal communication on classroom dynamics in Malaysian universities highlighted the importance of non-verbal cues such as body language, facial expressions, and eye contact in facilitating effective teacher-student communication. By deciphering these subtle cues, students can enhance their understanding of course material, engage more actively in class discussions, and forge stronger connections with their peers and professors.